Mental health training needs of physicians in Bangladesh: Views from stakeholders - Kamrun Nahar Koly; Enryka Christopher; Shahriar Ahmed; Cleo Baskin; Jobaida Saba; Md. Saiful Islam; Mohammad Raihan Tariq; Syeda Fatema Alam; Mst. Sadia Sultana; Monzia Mushtaq; Helal Uddin Ahmed (Elsevier, 2022)
Bangladesh is a lower-middle-income country with a high burden of mental health conditions and inadequate health systems. Prior research in similar settings has found that training physicians in mental health literacy can contribute to reducing the mental health treatment gap and strengthening the mental health care pathway. This study explores the need for mental health training for physicians by gathering stakeholders' perspectives and proposes recommendations for designing a mental training program in the context of Bangladesh.Key informant interviews were conducted among psychiatrists (n ​= ​9), and mental health entrepreneurs (n ​= ​7); one focus group discussion was conducted with psychologists (n ​= ​8); and one-on-one interviews were held with physician (n ​= ​17). Due to the COVID-19 restrictions, all interviews were conducted online, recorded and transcribed. Transcriptions were analyzed thematically, utilizing both an inductive and deductive approach.The data analysis from forty-one stakeholders generated three major themes and eight subthemes. Stakeholders perceived that the inadequate mental health system and low mental health awareness among physicians significantly contribute to the mental health treatment gaps. Stakeholders emphasized the need to include mental health training for physicians to increase skills related to identification and management of mental health conditions. Stakeholders suggested some basic components for the training content, feasible modalities to deliver the training, and implementation challenges. Recommendations included utilizing online training, ensuring interesting and practical content, and incorporating certification systems. At a systems level, stakeholders recommended including a mental health curriculum in undergraduate medical education, capacity building of other healthcare workers and increasing awareness at the policy level.There is clear agreement among stakeholders that implementing mental health training for physicians will promote universal health coverage and reduce the mental health treatment gap in Bangladesh. These findings can support creation of policies to strengthen the care pathway in countries with limited resources.